Voluntary alcohol intake in two rat lines selectively bred for learned helpless and non-helpless behavior - Vengeliene, Valentina; Vollmayr, Barbara; Henn, Fritz A.; Spanagel, Rainer (Psychopharmacology, 2005)
A high comorbidity between depression and alcoholism has been reported in several studies, but the mechanisms underlying this relationship remain unknown.
Published online: 2 October 2004
Gesehen am 03.11.2020